ASSESSMENT OF INDICATORS OF ANXIETY AND DEPRESSION IN PATIENTS AFTER COVID-19 (World Bulletin of Public Health, 2023)
The indicators of anxiety and depression of patients after Covid-19, which is one of the medical and social problems. The degree of anxiety and depression was assessed using modern neuropsychological scales. Based on the obtained results, an algorithm for early diagnosis was developed.
Keywords: Covid-19; anxiety; depression